Extracorporeal membrane oxygenation after protracted ventricular fibrillation cardiac arrest: case report and discussion. Issue 2 (March 2015) - Abu-Laban, Riyad B.; Migneault, David; Grant, Meghan R.; Dhingra, Vinay; Fung, Anthony; Cook, Richard C.; Sweet, David
Abstract: Extracorporeal membrane oxygenation (ECMO) is a method to provide temporary cardiac and respiratory support to critically ill patients. In recent years, the role of ECMO in emergency departments (EDs) for select adults has increased. We present the dramatic case of a 29-year-old man who was placed on venoarterial ECMO for cardiogenic shock and respiratory failure following collapse and protracted ventricular fibrillation cardiac arrest in our ED. Resuscitation efforts prior to ECMO commencement included 49 minutes of virtually continuous cardiopulmonary resuscitation (CPR), 11 defibrillations, administration of numerous medications, including a thrombolytic agent, while CPR was ongoing, percutaneous coronary intervention and stenting for a mid–left anterior descending coronary artery dissection and thrombotic occlusion, inotropic support, and intra-aortic balloon pump counterpulsation. Over the next 48 hours following ECMO commencement, the patient's cardiorespiratory function rapidly improved, and he was discharged home 9 days after admission with no neurologic sequelae. The history, indications, and increasing role of ECMO in a range of conditions, including cardiac arrest, are reviewed. RÉSUMÉ: L'oxygénation extracorporelle sur oxygénateur à membrane (OEOM) est un moyen de fournir une assistance cardiaque et respiratoire temporaire à des patients gravement malades. Le rôle de l'OEOM a gagné du terrain chez certains adultes aux services des urgences (SU) au cours des dernières années. Sera exposé ici le cas spectaculaire d'un homme de 29 ans, soumis à l'OEOM veino-artérielle pour un choc cardiogénique et une insuffisance respiratoire suivant un collapsus et un arrêt cardiaque causé par un accès prolongé de fibrillation ventriculaire, qui est survenu au SU de l'hôpital. Les moyens de réanimation mis en oeuvre avant le début de l'OEOM comprenaient des manoeuvres de réanimation cardiorespiratoire (RCR) pratiquées de façon quasi continue durant 49 minutes; 11 tentatives de défibrillation; l'administration de nombreux médicaments, dont un thrombolytique, pendant que se poursuivaient les manoeuvres de RCR; une intervention coronarienne percutanée et la pose d'une endoprothèse pour une dissection du segment moyen de l'artère interventriculaire antérieure et une oblité ration thrombotique; un soutien inotrope et la contrepulsion par ballon intra-aortique. Au cours des 48 heures suivant le dé but de l'OEOM, l'état cardiorespiratoire du patient s'est amélioré rapidement, et celui-ci est retourné chez lui 9 jours après son admission, et ce, sans souffrir de séquelles neurologiques. Seront passés en revue l'historique, les indications et le rôle de plus en plus grand de l'OEOM dans diverses affections, dont l'arrêt cardiaque.